Comparison between Anal Dilatation Protocols Following an Endorectal Pull-through for Hirschsprung Disease - Ruangtrakool, Ravit; Deepor, Jirarak (Siriraj Medical Journal, 2024)
Objective: The purpose of this study was to compare the mechanical obstruction rate following a transanal endorectal pull-through (TERPT) in patients with Hirschsprung disease, between regular anal dilatation (AD) and selective anal dilatation (NAD) which meant that dilatation was only performed when an obstructive symptom occurred. Materials and Methods: A retrospective chart review of patients with Hirschsprung disease who underwent TERPT/abdominal assisted TERPT at Siriraj Hospital between January 2009 and December 2021 was carried out. It was the surgeon’s preference that the dilatation protocols between the 2 groups (AD or NAD) were assigned. Mechanical obstructions included evidence of stricture, a clinical symptom of constipation, presence of Hirschsprung-associated enterocolitis (HAEC), and/or requirement of re-operation. Results: In total, 132 patients were included in this study, including 55 cases in the AD group (41.7%) and 77 cases in the NAD group (58.3%). Postoperative mechanical obstructions occurred in 84 patients (63.6%). Among the mechanical obstructions, there were 35 strictures (26.5%), 26 constipation (19.7%), 40 HAECs (30.3%), and 6 reoperation (4.5%). The mechanical obstruction rates in the AD [33/55 (60.0%)] and NAD [51/77 (66.2%)] groups were not significantly different (p = 0.582). The AD group was of a significantly younger age (p = 0.022) and lower body weight (p = 0.048) than the NAD group; however, a younger age and lower body weight were not significantly related with any of the obstructive complications. AD had a rate of anastomosis/cuff stricture [13/55 (23.6%)] similar to NAD [22/77 (28.6%)] (p = 0.665).